An Empirical Analysis Rejects the Hybrid Speciation Hypothesis of a Crucial Kiwifruit Species, Despite Genomic Evidence of Frequent Interspecific Gene Flow in the Genus - Yang, Jie; Fu, Weirui; Xu, Haoming; Song, Zhiping; Zhang, Wenju; Yang, Ji; Wang, Yuguo (Frontiers in Genetics, 2020)
Hybrid speciation is an important way to generate species diversity. In general, however, interspecific hybridization is easily confused with the formation of hybrid species. Using genomic resequencing data of the kiwifruit genus (Actinidia), at least ten species were documented recently as homoploid hybrid species, and thus a two-layer mode of species diversification has been proposed. As a crucial evidence, Actinidia fulvicoma was identified as a hybrid derivative of Actinidia eriantha × Actinidia cylindrica, representing a rare case of hybrid species in kiwifruit which won the competition of ecological niches with one of its putative parent species, A. cylindrica. However, the hypothesized hybrid origin of A. fulvicoma is inconsistent with our specimen observations. Here, we present multiple lines of evidence to reject the hybrid speciation hypothesis for this species, despite genomic evidence frequent interspecific gene flow. We collected the samples of A. fulvicoma in type locality and neighboring regions to contrast them with type specimen, and sequenced nuclear ribosomal DNA ITS, chloroplast trnL-trnF and mitochondrial nad2-i3, as well as four single-copy nuclear genes explored from kiwifruit genomes, to infer phylogenetic relationships among A. fulvicoma, its putative parental species and their relatives. Our data definitely reveal that A. fulvicoma occupies an independent backbone lineage and it is not a hybrid. This study suggests that correct evolutionary applications on extensive population surveys of the putative hybrid and its possible parents with strict criteria are necessary in the documentation of hybrid speciation to advance our understanding of the genomic basis of the hybrid species.